The Quality Of Ponorogo Chicken Satay Circulating In Malang City - Fradiana, Avida; Widati, Aris Sri; Rosyidi, Djalal (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
The purpose of this study was determine the quality of Ponorogo chicken satay circulating in Malang City. This research method used was a laboratory experimental using a Completely Randomized Design (CRD), with 3 treatments and 4 replications. The parameters were observed physical quality, chemical quality, and PAH (Polycyclic Aromatic Hydrocarbons). Data analysis used Analysis of Variance (ANOVA), if the data showed a significant difference, it was continued using the Duncan Multiple Range Test (DMRT) and descriptive of PAH (Polycyclic Aromatic Hydrocarbons). The results of the analysis of variance showed that the physical quality of Ponorogo chicken satay circulating in Malang City had no effect/ no significant difference (P>0.05) on pH, WHC, cooking loss, moisture content, protein content while fat content had a significant difference (P<0.05) and analysis of PAH (Polycyclic Aromatic Hydrocarbons) showed not detected. The quality of Ponorogo chicken satay circulating in Malang City still meets the requirements or safety standards for the consumption of chicken satay.Keywords: Ponorogo chicken satay, Malang City, physical quality, chemical quality, and Polycyclic Aromatic Hydrocarbons (PAH).